Disaster Management and Lessons from the Story of Prophet Noah: Integrating Structural and Non-Structural Approaches in Addressing Flood Risks - M. Kautsar Thariq Syah; Putri Lailatus Sa’adah (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to examine the occurrence of floods in the story of Prophet Noah as found in the Quran. A qualitative approach is chosen to gain a deep understanding of disaster management integration based on the narrative of Prophet Noah. The primary data source for this research is the Quran, specifically the chapters related to the story of Prophet Noah, supplemented by previous works exploring the Quranic perspective on disaster management. The data collection process involves a comprehensive literature review, gathering information from both primary and secondary sources. The research aims to understand the concept of disaster management, especially in the context of the story of Prophet Noah, by analyzing the Quranic text extensively to explore guidance and values related to disaster management. The data analysis consists of two main stages. Firstly, a narrative analysis is conducted to identify the steps taken by Prophet Noah in facing the flood disaster and exploring values that can be adopted in the context of contemporary disaster management. Secondly, a comparative analysis is conducted with previous research to highlight similarities and differences in the findings. Limitations of the study involve interpretations and religious contexts, with a primary focus on the story of Prophet Noah in the realm of disaster management. The research findings are expected to be translated into practical recommendations, enriching contemporary disaster management approaches. Overall, this study aims to provide valuable insights into the potential application of Prophet Noah's narrative for understanding and enhancing disaster management amid ongoing global changes.